TECTONIC STRESS FIELD AND MODERN MOVEMENTS IN THE EARTH’S CRUST IN THE EAST SEA REGION - Luong, Nguyen Van; Que, Bui Cong; Duong, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2008)
In this paper, characteristics of tectonic stress field and modern movements in the Earth’s crust of the East Sea have been studied on the basis of analysing focal mechanism data of 25 moderate and large earthquakes occured in the region. It is shown that, the tectonic stress field of studied region is rather complicatedly differential, in which the compressive stress axis varies from the orientation of sub-latitude in the northeast East Sea to sub-longitude in the Hainan island area and northwest-southeast in remain areas. In such a tectonic stress field, almost sublatitudinal and sublongitudinal faults are characterised by mordern movements of left- and right lateral strike-normal dip slip types, while the South Hainanfaults are of left lateral strike-normal dip type. In addition, thrust- and normal dip slip movements are also excavated in sublongitudinal and sublatitudinal fault systems in the Central East Sea deep depression and basin system of the Northestern East Sea.